Impact of a continuing medical education program on primary care providers - an analysis of a child psychiatry education program in Saskatchewan - Malin Clark; Madhav Sarda; Mariam Alaverdashvili; Thuy Le; Adrian Teare; James Barton; Peter S. Jensen; Anna Felstrom (BMC Primary Care)
Abstract Background Treating children and youth with mental health problems in the primary care setting is challenging for many reasons. One barrier to care is a lack of physician knowledge of child psychiatry. Saskatchewan has implemented a 6-month course developed by the non-profit REACH Institute and adapted to Canada (CanREACH), focused on teaching and implementing evidence-based child psychiatric diagnostic and treatment methods into primary care. Our study focused on determining this program’s impact on primary care providers (PCPs) and patients. Methods To determine the impact of CanREACH, we assessed the knowledge and skills gained by PCPs and determined whether these were retained over time. To evaluate systemic impact, we examined if the pre-training and post-training referrals to an outpatient child psychiatry clinic were impacted for PCPs who had taken the course. Results PCPs developed significant skills and comfort in assessing, diagnosing and treating various mental illnesses and retained this knowledge over time. PCPs who had taken the course had a significant reduction in referrals (0.9 per PCP) made to child psychiatry, as compared to those who had not taken the course (1.3 per PCP) (p < 0.05). This long-term retention of skills provides reassurance about the effectiveness of the CanREACH program. Conclusions Education improved the capacity of primary care providers to manage child and adolescent psychiatry cases, reducing the need to refer children to psychiatry subspecialists. This ultimately improved access to outpatient child psychiatry care for Saskatchewan residents.